Integrated approach for smart implantable cardioverter defibrillator (ICD) device with real time ECG monitoring: use of flexible sensors for localized arrhythmia sensing and stimulation - Puri, Munish; Chapalamadugu, Kalyan C.; Miranda, Aimon; Gelot, Shyam; Adithya, Prashanth C.; Tipparaju, Srinivas M. (Frontiers in Physiology, 2013)
Arrhythmias are the most common cause of death associated with sudden death and are common in US and worldwide. Cardiac Resynchronization Therapy (CRT), evolving from pacemakers and development of Implantable Cardioverter Defibrillator (ICD), has been adopted for therapeutic use and demonstrated benefits in patients over the years due to its design and intricate functionality. Recent research has been focused on significant design improvement and efforts are dedicated towards device size reduction, weight and functionality in commercially available ICD’s since its invention in the 1960’s. Commercially available CRT-D has shown advancement on both clinical and technical side. However, improved focus is required on the device miniaturization, technologically supported and integrated wireless based system for real time heart monitoring electrocardiogram (ECG). In the present report a concise overview for the state-of-the art technology in ICDs and avenues for future development are presented. A unique perspective is also included for ICD device miniaturization and integration of flexible sensing array. Sensor array integration along with its capabilities for identifying localized arrhythmia detection and targeted stimulation for enhancing ICD device capabilities is reviewed.